Alkaloid caulerpin and cytotoxic activity against NCL-H460 lung cancer cells isolated along with β-sitosterol from the Halimeda cylindracea decaisne - Dini, Iwan; Soekamto, Nunuk Hariani; Firdaus,; Supratman, Unang; Jalifah Latip, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Alkaloid caulerpin (1), along with β-sitosterol (2), were isolated from the n-hexane extract of the macroalga Halimeda cylindracea Decaisne. The chemical structure was identified by a spectroscopic method including IR, MS, UV, NMR 1D, NMR 2D, and comparison with data of spectra previously reported. Compounds (1) and (2) were isolated for the first time from this macroalga. Compund (1) were evaluated for their cytotoxicity activity against NCL-H460 lung cancer cells in vitro and showed moderate activity with IC50 value of 20.05 μg/mL.